Video Edukasi Stop Bulliying Untuk Meningkatkan Pengetahuan Siswa Terhadap Kesehatan Mental - Mizam Ari Kurniyanti; Tania Laurenshia Gita Kaabah; Riska Febriyanti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Bullying is violence committed by individuals or groups both physically and psychologically againstpeople who are unable to protect themselves. SMK Adi Husada is one of the high schools located in thecentre of the city of Malang and students are enrolled from various regions in the city of Malang andfrom different economic levels, causing considerable heterogeneity between students, and it is one of thefactors that cause bulliying at SMK Adi Husada. Community service at SMK Adi Husada aims to help theschool by providing knowledge to students about the impact of bullying through the provision ofeducational videos and counselling about bullying, with the hope of increasing students' knowledgerelated to the problem of bullying and providing explanations related to the impact of bullying that canoccur both on the perpetrator and the victim